SAP2000: Priročnik za začetno uporabo pri linearni statični analizi ravninskih linijskih konstrukcij - Imamović, Denis (University of Maribor Press, 2023)
SAP2000: Basic User’s Guide for Linear Static Analysis of Planar Line Structures. The SAP2000 program is an extremely powerful tool for mechanical analyses and structural design in practice. It also proved to be excellent for study purposes, in the preparation of seminar and final works, as well as in the control of the results of “by hand” mechanical analyses, which students become familiar with during their many years of study at Faculty of Civil Engineering, Transportation Engineering and Architecture (FGPA) in Maribor. For this purpose, a manual entitled “SAP2000: Basic user’s guide for linear static analysis of planar line structures” has been prepared for all students of the FGPA who are interested in working in the SAP2000 program. In this work, for the most basic mechanical - linear static - analysis, all the intermediate steps from the initial modeling to the final presentation of the results are comprehensively and graphically presented on three simple examples. As such, the manual is intended for users with basic knowledge of mechanics without any prior experience in the SAP2000 program.